Why philanthropy matters : how the wealthy give, and what it means for our economic well-being - Ács, Zoltán J. (Princeton University Press, 2013)
"Philanthropy has long been a distinctive feature of American culture, but its crucial role in the economic well-being of the nation--and the world--has remained largely unexplored. Why Philanthropy Matters takes an in-depth look at philanthropy as an underappreciated force in capitalism, measures its critical influence on the free-market system, and demonstrates how American philanthropy could serve as a model for the productive reinvestment of wealth in other countries. Factoring in philanthropic cycles that help balance the economy, Zoltan Acs offers a richer picture of capitalism, and a more accurate backdrop for considering policies that would promote the capitalist system for the good of all."--Publisher's description.